2011
DOI: 10.1016/j.cub.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 Controls the Trafficking of Notch and Sanpodo toward E-Cadherin Junctions in Sensory Organ Precursors

Abstract: In Drosophila melanogaster, external sensory organs develop from a single sensory organ precursor (SOP). The SOP divides asymmetrically to generate daughter cells, whose fates are governed by differential Notch activation. Here we show that the clathrin adaptor AP-1 complex, localized at the trans Golgi network and in recycling endosomes, acts as a negative regulator of Notch signaling. Inactivation of AP-1 causes ligand-dependent activation of Notch, leading to a fate transformation within sensory organs. Los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(132 citation statements)
references
References 44 publications
(61 reference statements)
7
122
1
1
Order By: Relevance
“…5A-CЈ). Although the Rab11 function during pI cell division has not been directly tested owing to its role in cytokinesis, several findings indicate that the Delta ligand transits the Rab11 endosome to reach the pI daughter cell interface to promote Notch signalling and the specification of the pIIa cell fate (Benhra et al, 2011;Benhra et al, 2010;Emery et al, 2005;Jafar-Nejad et al, 2005). Accordingly, we observed that fluorescently labelled internalized 2663 RESEARCH ARTICLE Centrosome movement regulation Delta antibodies can be found localized around the anterior pI centrosome during cytokinesis (Fig.…”
Section: Crmp Controls the Duration Of Rab11 Accumulation Around The mentioning
confidence: 78%
See 2 more Smart Citations
“…5A-CЈ). Although the Rab11 function during pI cell division has not been directly tested owing to its role in cytokinesis, several findings indicate that the Delta ligand transits the Rab11 endosome to reach the pI daughter cell interface to promote Notch signalling and the specification of the pIIa cell fate (Benhra et al, 2011;Benhra et al, 2010;Emery et al, 2005;Jafar-Nejad et al, 2005). Accordingly, we observed that fluorescently labelled internalized 2663 RESEARCH ARTICLE Centrosome movement regulation Delta antibodies can be found localized around the anterior pI centrosome during cytokinesis (Fig.…”
Section: Crmp Controls the Duration Of Rab11 Accumulation Around The mentioning
confidence: 78%
“…Neur promotes Delta endocytosis in the anterior pI daughter cell (Benhra et al, 2010;Le Borgne and Schweisguth, 2003b). The Delta recycling to the apical pIIa/pIIb interface is then accomplished through the Rab11 positive endosomes (Benhra et al, 2011;Benhra et al, 2010;Emery et al, 2005). Among other activities, Delta recycling requires the exocyst complex and the formation of apical actin-rich (ARS) structure at the level of the apical midbody, which forms upon pI cytokinesis (Jafar-Nejad et al, 2005;Langevin et al, 2005b;Rajan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numb carries out these functions via regulating endocytic trafficking of several key molecules, such as Notch, sanpodo, cadherins and integrins [4,7,9,14,17,18,23,24,26,51,52]. Although in all these contexts Numb functions as an endocytic adaptor protein, the exact role of Numb in endocytic trafficking remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…These observations strongly suggest that N endocytosis was impaired in ␣-ada or numb mutant IPs and NBs. More direct proof of altered N endocytosis in ␣-ada or numb mutant IPs may come from a live antibody uptake assay, as done in other tissues (34,37,48,49). However, the thickness of whole brain tissues has so far posed a technical challenge for this approach.…”
Section: Inactivation Of Ap-2 Complex Subunits Resulted In Ectopicmentioning
confidence: 99%